Brazilian advanced specialty programs in endodontics: characteristics and distribution - Reolon, Matheus Luis; Grock, Camila Hélen; Grazziotin-Soares, Renata; Montagner , Francisco (Revista da ABENO, 2022)
The existence of several Endodontics specialty programs in Brazil is known. However, there was no precise information regarding their geographic distribution, duration, workload and the profiles of the program’s directors. There was also no means to determine if the requirements defined by the country’s legal bodies were fulfilled by the institutions. The present cross-sectional study was conducted to bring together characteristics and peculiarities of all Brazilian endodontics advanced specialty programs, searching for information on the regulatory-agencies webpages and other venues. We searched the Ministry of Education’s website to locate information such as geographical location, duration (months), number of hours, and program director professional degree profile. Program’s homepages were searched to collect additional information – frequency, periodicity, costs, number of faculties. The searches were made between August 2019 and October 2019, identifying 505 registered programs and 117 specific program’s websites. It was observed that 39% of the programs are in the Southeast region and 61.2% have a duration of 24 months. Additionally, a majority of the program’s directors were male, accounting for 69.1% of the sample. The most common highest qualification held by them was a Masters’ degree (45.1%). Regarding the 117 programs that had specific websites, they presented insufficient information, for instance: the frequency was only reported in 81 programs/websites, the number of teachers only in 51, and total fees only in 65. It was concluded that there are various Endodontic specialization programs in Brazil, benefiting the different students’ profiles. Also, there is a lack of clear information on some programs.